Hubungan Dukungan Keluarga dengan Kepatuhan Konsumsi Tablet Fe pada Ibu Hamil di Puskesmas Botolinggo - Susanti, Heni; Ekasari, Tutik; Supriyadi, Bagus (Universitas Nurul Jadid, 2024)
Non-compliance of pregnant women in consuming iron tablets (Fe) is caused by several factors, such as forgetfulness, fear of large babies, low awareness of the importance of iron supplements, insufficient understanding of the dangers of anemia for pregnant women and infants, as well as side effects like nausea or dizziness after taking iron tablets. This study aims to determine the relationship between family support and compliance in consuming iron tablets among pregnant women at Botolinggo Health Center, Bondowoso Regency, in 2023. A cross-sectional design was used in this study, with a population of all pregnant women who underwent check-ups at Botolinggo Health Center, totaling 60 individuals. The sample consisted of 30 pregnant women, selected using accidental sampling. The results showed that pregnant women who complied with iron tablet consumption had good family support, while non-compliance was associated with a lack of family support. A total of 60% or 18 respondents who did not comply with iron tablet consumption reported insufficient family support. The Spearman's rho test results showed a P value of 0.003, indicating a significant relationship between family support and compliance with iron tablet consumption among pregnant women at Botolinggo Health Center.